PENERAPAN PEMBELAJARAN BERBASIS PROJECT BASED LEARNING BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Rambe, M. Si, Isnaini Halimah; Octariani, Dhia; Wandari, Ria; Adlina, Zuraidah (MES: Journal of Mathematics Education and Science, 2024)
This research aims to determine the results of implementing GeoGebra-assisted Project Based Learning in terms of students' learning interest. Implementation of a learning model in the form of a project to be implemented individually or in groups and implemented within a certain period of time. This research used a classroom action research (CAR) method by taking the subject of research of class XI students of SMA Swasta Budisatrya Medan consisting of 30 students. Based on this research, the results showed that the interest in learning students from cycle I was 52.2% and in cycle II by 69% overall increased. While the learning outcomes of students increased by an average of 62.81 in cycle I increased to 85.34 in cycle II while the percentage of completeness was 46.67% in cycle I increased to 76.67% in cycle II. It was concluded that in this research the implementation of PjBL learning assisted by GeoGebra in mathematics learning was able to increase the interest and learning outcomes of students